Conceptions of a teacher in his ways to perceive the exercise of investigation from his practice - Gutiérrez-Rico, Dolores; Almaraz-Rodríguez, Omar David; Bocanegra-Vergara, Netzahualcóyotl (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This investigation is a phenomenological study, which aims to understand the conceptions that the teacher has about educational research. They were used as techniques for data collection, open interview and videos. The contexts of study were three congresses: one international, one national and one state. The central categories that arose once the information was analyzed are: Culture of research, professional education in research, educational research as an improvement in the resolution of problems, beliefs and conceptions of research from different contexts. It is concluded that the main interest was determined by the meaning that the research teachers attributed to their experiences, given the specific contexts where they work. In addition, they believe that research is necessary in and from reality in the classrooms that meet the needs of the educational actors affected by institutional practices.